Changes in Knowledge, Skills, and Confidence in Fieldwork Educators After an Evidence-Based Practice Short Course - Alison Nichols (Scholarworks @ WMU, 2017)
Background: It is critical that fieldwork educators demonstrate effective use of evidence for clinical decision making so that occupational therapy (OT) students learn to apply concepts from the classroom to everyday practice. Method: OT fieldwork educators completed a 3-hour short course designed to provide instruction on the first three steps of the evidence-based practice (EBP) process: developing a clinical question, searching the literature, and assessing the evidence. The participants completed a pretest on site and post-test 3 weeks after the course to assess their knowledge, skills, and confidence when using EBP. The Adapted Fresno Test was used to measure knowledge and skills, and the Evidence-Based Practice Confidence Scale measured confidence. Results: Fourteen OT practitioners completed the short course and pretest; nine returned the post-test, and six answered all of the questions. These six participants improved their knowledge and skills (3.75%) and their confidence (17.99%) from pretest to post-test. Conclusion: Fieldwork educators showed improvements in their knowledge, skills, and confidence when using EBP after a 3-hour introductory course. This could lead to improved modeling of appropriate EBP behaviors for OT students, promoting the translation of knowledge from classroom to clinic.